Development of Supply Chain Management in Russian Catering Industry: Trends and Prospects in Post-Crisis Conditions - Alim B. Nagoev; Vita A. Grekova; Olga G. Kovalenkova; Julia ?. Oleynikova; Yaha A. Khadueva (International Journal of Supply Chain Management, 2020)
Abstract- The importance of the current study is due to the fact that, despite external unfavorable economic and political factors, Russian food industry has seen a stable growth by supply chain management for more than a decade, having a positive impact on related industries. However, sanctions and external restrictions imposed by Western countries on Russia have direct or indirect negative effects on Russian food industry which is one of the structure-forming sectors of the national economy. In this regard, search for effective methods of minimizing this negative impact is relevant and timely. The goal of the study is to identify new approaches in supply chain strategy to progressive development of public catering in the context of external sanctions, and a general decrease in the economic activity of food market entities. The results of previous studies of foreign and Russian researchers in the field of public catering problems have been used in this research. It was found that despite the measures that can bring this industry to a new level of development, many players must leave the food industry market. It is proved that moving to the lower price categories may be a good solution in order to save the business in crisis conditions; however, many participants will have to leave the catering market, and larger market players should change their behavior strategy.